2011
DOI: 10.1111/j.1365-3040.2011.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of reactive oxygen species and reactive nitrogen species in pepper (Capsicum annuum L.) plants under low temperature stress

Abstract: Low temperature is an environmental stress that affects crop production and quality and regulates the expression of many genes, and the level of a number of proteins and metabolites. Using leaves from pepper (Capsicum annum L.) plants exposed to low temperature (8°C) for different time periods (1 to 3 d), several key components of the metabolism of reactive nitrogen and oxygen species (RNS and ROS, respectively) were analysed. After 24 h of exposure at 8°C, pepper plants exhibited visible symptoms characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
156
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(170 citation statements)
references
References 113 publications
(208 reference statements)
13
156
1
Order By: Relevance
“…Cold temperature will bring plants into an oxidative stress and it was shown that APX activity was up-regulated in plants such as rice (Oidaira et al, 2000), Coffea (Fortunato et al, 2010), haw (Eltelib et al, 2011), and pepper (Airaki et al, 2012) when subjected to low temperature. This is thought to be a normal defense reaction when plants are subjected to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Cold temperature will bring plants into an oxidative stress and it was shown that APX activity was up-regulated in plants such as rice (Oidaira et al, 2000), Coffea (Fortunato et al, 2010), haw (Eltelib et al, 2011), and pepper (Airaki et al, 2012) when subjected to low temperature. This is thought to be a normal defense reaction when plants are subjected to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Low temperature stress induced the accumulation of reactive oxygen species (ROS) such as superoxide, hydrogen peroxide, and hydroxyl radicals (Suzuki and Mittler, 2006;Farooq et al, 2009). These ROS may be signals inducing ROS scavengers and other protective mechanisms, as well as damaging agents contributing to stress injury in plants (Xiong et al, 2002;Airaki et al, 2012;Li et al, 2013;;Farooq et al, 2016)). Diverse plant species tolerate cold stress to a varying degree, which depends on reprogramming gene expression to modify their physiology, metabolism, and growth (Chinnusamy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al (2011) observed a continual increase in the formation of superoxide anion in strawberry leaves under low temperature up to 48 hours, decreasing after that. During acclimatization of Capsicum annum seedlings to low temperature, Airaki et al (2012) observed an increase in the level of the non-enzymatic antioxidants ascorbate and glutathione and in the activity of the NADPH dehydrogenase.…”
Section: Resultsmentioning
confidence: 99%
“…Plants under abiotic stress conditions, such as drought, salinity, and high and low temperatures, produce reactive oxygen species (ROSs), as observed by Luo et al (2011), in which low temperature continually increased the formation of superoxide anion and hydrogen peroxide in leaves of Fragaria ananassa Duch., Zoji and Toyonaka cultivars, up to 48 hours, decreasing after that. Airaki et al (2012) observed an increase in the level of the non-enzymatic antioxidants ascorbate and glutathione and in the activity of the enzyme NADPH dehydrogenase during acclimatization of Capsicum annum L. plants, indicating the action of these substances in the cell antioxidant system. Even in storage under low temperature, there is production of superoxide anion and hydrogen peroxide, as observed by Pukacka and Ratajczak (2005) in Fagus sylvatica seeds stored at temperatures of 4, 20 and 30 ºC.…”
Section: Introductionmentioning
confidence: 94%